PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI TEMA 5 SUBTEMA 2 KELAS 6 UNTUK MENINGKATKAN PEMAHAMAN SISWA DI SD - Meri Agustina; Yusni Arni; Annisa Rahman Permata Sari; Asyifa Nabila (STKIP Subang, 2024)
This research is development research which aims to develop animated video-based learning media using the method (Research and Development) with the ADDIE model which has 5 stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation). In science and science learning theme 5, subtheme 2. The subjects of this animated video media development are students of class 6 B, SDN 50 Palembang. The test results by asking several questions showed that all class 6 B students understood the material well. What can be seen is that all students can answer well and are very enthusiastic about the questions we ask. Thus we can conclude that users of animated video-based learning media can increase students' understanding in the learning process.